The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/03000605221086442
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of in-hospital mortality after acute upper gastrointestinal bleeding: cross-validation of several risk scoring systems

Abstract: Objective We aimed to identify the clinical, biochemical, and endoscopic features associated with in-hospital mortality after acute upper gastrointestinal bleeding (AUGIB), focusing on cross-validation of the Glasgow-Blatchford score (GBS), full Rockall score (RS), and Cedars-Sinai Medical Center Predictive Index (CSMCPI) scoring systems. Methods Our prospective cross-sectional study included 156 patients with AUGIB. Several statistical approaches were used to assess the predictive accuracy of the scoring syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…A multicenter study which assessed the accuracy of 5 scores (GBS, Pre-RS, full-RS, AIM65, and PNED) for both intervention and mortality found that GBS was superior in predicting intervention or death [ 34 ]. Another study which analyzed the performance of 3 scores (GBS, full Rockall score and CS) for the prediction of in-hospital mortality found that all scores had an AUC > 0.9 but CS was superior to RS and GBS [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A multicenter study which assessed the accuracy of 5 scores (GBS, Pre-RS, full-RS, AIM65, and PNED) for both intervention and mortality found that GBS was superior in predicting intervention or death [ 34 ]. Another study which analyzed the performance of 3 scores (GBS, full Rockall score and CS) for the prediction of in-hospital mortality found that all scores had an AUC > 0.9 but CS was superior to RS and GBS [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Upper gastrointestinal bleeding (UGIB) represents a common cause of hospital admissions in the gastroenterology and intensive care unit (ICU), with mortality ranging from 3 to 15% [ 1 , 2 , 3 , 4 ]. In most cases, early treatment and early endoscopy during the first 24 h is recommended according to current guidelines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, these models often include kidney failure and/or markers altered in kidney disease as inputs, and thus can yield convoluted insights in the dialysis population. 36-40 The appropriate identification and risk classification in patients with kidney failure remains a clinical challenge. The Glasgow Blatchford score (GBS) has been evaluated for predicting the need for admission and endoscopic intervention in kidney failure patients presenting to the hospital with a suspected GIB; this model was found to have reasonable performance (AUROC=0.63, sensitivity=81.2%, and specificity=42.3%) with a GBS cutoff score of ≥14.…”
Section: Discussionmentioning
confidence: 99%
“…A la actualidad de hace uso de scores debidamente validados que tienen utilidad en la toma de decisiones para el manejo del sangrado gastrointestinal (19)(20)(21), entre ellos y de amplio uso tenemos la escala Glasgow Blatchford, cuyo objetivo es identificar pacientes con hemorragia digestiva alta de alto o bajo riesgo de necesidad de manejo de este sangrado, con sensibilidad 99% y especificidad 32%, el punto de corte es 2; es decir pacientes con un puntaje <2 son de bajo riesgo y pueden ser dados de alta, en cambio pacientes con un puntaje > 2 son catalogados como de alto riesgo, y deben ser admitidos para manejo de la hemorragia digestiva. Dentro los parámetros de este score se encuentran urea sérica, hemoglobina, presión arterial, pulso, tacto rectal positivo para melena, este último con un puntaje de 1 pudiendo ser determinante para establecer el tratamiento endoscópico del sangrado gastrointestinal (22).…”
Section: Pregunta De Investigaciónunclassified